Coconut shell charcoal briquettes production using banana corm adhesive - Fahyuddin; Remi Ayu Pratika; Fery Indradewi Armadany (The Indonesian Chemical Society, Chapter Nusa Tenggara and The University of Mataram, 2025)
The production of biomass-based briquettes from coconut shell charcoal and banana corm adhesive has been successfully carried out. This research aims to determine whether the banana corm may serve as an adhesive for briquette production from coconut shell charcoal. The concentration of banana corm utilized as adhesive is 10, 20, 30, 40, and 50%. For comparison analysis, this study also employed tapioca flour adhesive with the same concentration. The briquettes adhere to the SNI 01-6235-2000 standard for briquettes. The quality of briquettes is determined based on fixed carbon content and calorific value. The minimum standard calorific value and fixed carbon content are 5000 cal/g and 65%, respectively. Briquettes with a 90:10 ratio (coconut shell charcoal to banana corm adhesive ratio) had the highest calorific value of 7250 cal/g and fixed carbon content of 80.04%. In comparison, the tapioca flour adhesive provides a calorific value and fixed carbon content of 6995 cal/g and 81.09%, respectively. Furthermore, another indicator that determines briquette quality is the content of moisture, ash, and volatile matter. Briquettes with a 90:10 ratio possessed low moisture content (3.55%), ash content (6.45%), volatile matter content (9.96%), and burning rate (0.020 g/sec). This result indicates that the briquettes with a 90:10 ratio exhibit the greatest quality. Briquettes with banana corms adhesive have similar characteristics to tapioca flour, especially in terms of calorific value. As a result, the highlight of this research lies in offering banana corm, which has scientific contribution and future potential as an alternative adhesive in the briquetting process